PRESTASI BELAJAR ANAK DALAM KELUARGA MARGINAL DI DESA MERANGIN KECAMATAN KUOK KABUPATEN KAMPAR - Muhammad Iqbal; Jonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research was conducted in the village of Kampung Long Merangin Kuok District of Kampar regency. how socio-economic conditions of the working population as a mountain rock-breaking and self-employed in the village of Kampung Long Merangin Kuok District of Kampar regency. This study entitled "Children in Family Learning Achievement Marginal In the village of Kuok Merangin District of Kampar regency". Topics focus of this research is how the learning achievement of children in the family stone-crushing mountain in the village of Kuok Merangin District of Kampar regency. Samples from this study is that people are classified into families breaking stones Mountains. Pengambikan samples was done by simple random sampling technique. Samples are numbered 10 family heads mountain rock breaker. The author uses qualitative descriptive method and the data was analyzed qualitatively. Data instrument is observation, interviews, questionnaires and documentation. The results showed that the socio-economic life of the respondents rely on the natural, economic respondents rooted in the rocks of the mountain. Due to insufficient income to meet the needs of their families reponden cause children's education respondents tend terbangkalai family. However, some respondents prioritize education for their families. They finance their children's education although they had owed to neighbors, friends and relatives. Children's achievement in marginal families in the village Merangin very satisfactory in the majority of respondents. Many family child respondents have satisfactory progress, despite the lack of funds did not make their child's desire to recede in continuing education and improve their family educationKata kunci: Marginalisasi, education and famil